The Complement C3a and C3a Receptor Pathway in Kidney Diseases - Gao, Shuang; Cui, Zhao; Zhao, Ming-hui (Frontiers in Immunology, 2020)
The pathogenesis of some kidney diseases is closely associated with complement activation, of which C3a/C3aR might play a crucial role. C3a/C3aR has bipolar roles, it exerts anti-inflammatory or pro-inflammatory in different cell types and different diseases. In kidneys, C3aR is expressed on the tubular epithelium and less expressed on the glomerular podocytes. C3aR expression is enhanced and the levels of C3a in plasma and urine are increased in many kinds of kidney diseases, which are associated with disease progression and severity. C3a/C3aR facilitates the progression of glomerular and tubulointerstitial diseases, while it has opposite effects on urinary tract infections. The clinical trials of C3a/C3aR in kidney diseases are deficient. Here we reviewed the studies of C3a/C3aR in kidney disease, with the aim to understanding its controversial roles in-depth and its potential therapeutic values.